2021
DOI: 10.3390/horticulturae7100400
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate Treatment Affects Fruit Quality and Also Alters the Composition of Metabolites in Strawberries

Abstract: This study evaluated the effect of preharvest treatments with salicylates (salicylic acid (SA), methyl salicylic acid (MeSA) and acetyl salicylic acid (ASA)) on fruit quality parameters and primary and secondary metabolites during ripening at five sampling dates. The results showed that salicylates affect overall fruit quality, and some very desirable and important properties of strawberry fruits were acquired by the treatments, such as a deeper red colour (decreased hue angle), delayed ripening process with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(106 reference statements)
1
5
0
Order By: Relevance
“…Kumar et al [25] reported in strawberry that salicylic acid played a effective role on mitigating ascorbic acid oxidase enzyme activity that oxidize ascorbic acid to dehydroascorbic acid which hastened the ascorbate peroxidase and glutathione reductase activity and also accumulates reducing sugars. This statement is in accordance with [26][27][28].…”
Section: Ascorbic Acid Content (Mg/100g)supporting
confidence: 80%
“…Kumar et al [25] reported in strawberry that salicylic acid played a effective role on mitigating ascorbic acid oxidase enzyme activity that oxidize ascorbic acid to dehydroascorbic acid which hastened the ascorbate peroxidase and glutathione reductase activity and also accumulates reducing sugars. This statement is in accordance with [26][27][28].…”
Section: Ascorbic Acid Content (Mg/100g)supporting
confidence: 80%
“…The fact that the healthy tissue had a higher content of flavonols than the boundary tissue around the lesion caused by the fungus M. laxa could be crucially influenced by the treatment with salicylates, since in the case of the curative use of the solutions, a significant difference between the treated and untreated fruits was revealed. It is already known that salicylates increase the content of flavonols in strawberries [17], apple fruit [21], apple leaves [22] and grape berries [48]. The results for preventive use of solutions are less clear, with the exception of treatment with MeSA.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that treatment with SA can affect different fruit properties, such as fruit quality. Among other things, it can improve fruit color, fruit weight, fruit firmness, vitamin C content and sugar content in strawberries [17]. SA also affects the accumulation of bioactive compounds [18][19][20] through the phenylpropanoid metabolic pathway and induction of its key enzymes, such as phenylalanine ammonia-lyase (PAL), chalcone synthase/chalcone isomerase (CHS/CHI), flavanone 3β-hydroxylase (FHT) and dihydroflavonol 4-reductase (DFR) and consequently causes changes in the accumulation of some important phenolic groups, such as flavanols, flavonols, hydroxycinnamic acids and, within these, some individual phenolic compounds, such as procyanidins, chlorogenic acid and cyanidin-3-O-galactoside [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC conditions and equipment for both analyses were based on Gačnik et al (2021) [ 52 ]. They are shown in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of individual phenolics was performed by high-performance liquid chromatography (HPLC; Thermo Scientific; San Jose, CA, USA) with a DAD detector set to 280, 350, and 530 nm wavelengths. Protocols were performed as described by Gačnik et al (2021) [ 52 ]. The HPLC conditions and equipment used for the analysis of phenolic compounds are shown in Table S1 .…”
Section: Methodsmentioning
confidence: 99%